Sustainability in coffee production in Kenya - Waswa, Boaz (2025)
The presentation highlights strategies for building sustainability in the coffee systems in Kenya. It highlights the Coffee sector and productions systems in Kenya and discusses regenerative agriculture practices that can help improves soil health, conserve biodiversity, and adapt to changing climate and improve productivity and incomes for coffee farmers. The presentation was made as part of the knowledge sharing for the Aiducation and the Swiss Study Foundation Summer School on "Brewing a Sustainable Future in the Global Coffee Chain" in Nairobi, 2025. This dialogue aligns with work at the Alliance Bioversity CIAT on coffee regenerative agriculture under the IDH Coffee Farmers Income Resilience Program, the Sustainable Farming Science Program and the Central Highlands Ecoregion Foodscape (CHEF) by The Nature Conservancy.